2014
DOI: 10.1111/1460-6984.12133
|View full text |Cite
|
Sign up to set email alerts
|

Word structures of Granada Spanish‐speaking preschoolers with typical versus protracted phonological development

Abstract: The current study provides preliminary reference data for word structure development in a Spanish variety with restricted coda use, both by age and types of word structures. Between ages 3 and 5 years, global measures (whole word match, word shape match) distinguished children with typical versus protracted phonological development. By age 4, children with typical development showed near-mastery of word structures, whereas 4- and 5-year-olds with PPD continued to show syllable deletion and cluster reduction, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
3
6
0
7
Order By: Relevance
“…In turn, Vergara et al ( 2020 ) found higher matching percentages in Chilean TD 4-year-olds. Results on medial codas can be compared with percentage of matches in heterosyllabic groups (C1 being a medial coda) from the study by Bernhardt et al ( 2015 ): TD children between 3 and 5 years of age showed FM percentages ranging 85–100%, while FM percentages in children with PPD of similar ages ranged 65–80% in line with findings in the present study. However, previous comparisons of phonological profiles of DS with those of children with phonological disorders yielded mixed results: Parsons and Iacono ( 1992 ) claimed that phonological processes did not differ from other phonologically-impaired populations, while inconsistent production of words appeared to be different from children with phonological disorder in the study by Dodd and Thompson ( 2001 ).…”
Section: Discussionsupporting
confidence: 90%
“…In turn, Vergara et al ( 2020 ) found higher matching percentages in Chilean TD 4-year-olds. Results on medial codas can be compared with percentage of matches in heterosyllabic groups (C1 being a medial coda) from the study by Bernhardt et al ( 2015 ): TD children between 3 and 5 years of age showed FM percentages ranging 85–100%, while FM percentages in children with PPD of similar ages ranged 65–80% in line with findings in the present study. However, previous comparisons of phonological profiles of DS with those of children with phonological disorders yielded mixed results: Parsons and Iacono ( 1992 ) claimed that phonological processes did not differ from other phonologically-impaired populations, while inconsistent production of words appeared to be different from children with phonological disorder in the study by Dodd and Thompson ( 2001 ).…”
Section: Discussionsupporting
confidence: 90%
“…El cambio de nomenclatura se debe a una preferencia por un concepto centrado en la normalidad y no en el déficit, pues existe la posibilidad de que los niños alcancen el desarrollo típico (DT). A partir de esto, diversas investigaciones han buscado caracterizar dicha condición a nivel lingüístico y comportamental (Bernhardt et al, 2015;Burrows & Goldstein, 2010;Dubasik & Ingram, 2013;Goldstein, Fabiano, & Iglesias, 2004;Mason, 2015;Raymond, 2017). Dubasik & Ingram (2013) compararon el rendimiento lingüístico de seis niños monolingües hablantes de español nacidos en Estados Unidos, de entre 3.7 y 3.11 años, de los cuales tres presentaban DFP y tres DT.…”
Section: Desarrollo Fonológico Prolongado (Dfp)unclassified
“…La fonología no lineal ha permitido incorporar nuevos enfoques al análisis fonológico infantil en las unidades suprasegmentales y las unidades segmentales. Dentro de las unidades suprasegmentales se encuentran: (1) Coincidencia Palabra Completa, en inglés Whole Word Match (WWM), que se refiere a la proporción de palabras producidas por un niño que coinciden con el modelo adulto (Bernhardt et al, 2015), (2) Coincidencia de Estructura de la Palabra o Word Shape Match (WSM) en inglés, parámetro que mide la proporción de palabras producidas por el niño que, según la estructura silábica, coinciden con el modelo adulto (Bernhardt et al, 2015) y (3) acento prosódico, rasgo fundamental que se puede definir como el mayor grado de prominencia de una sílaba con respecto a las otras dentro de una misma palabra (Real Academia Española, 2011). Por su parte dentro de las unidades segmentales se encuentra el porcentaje de consonantes correctas (PCC) producidas por los menores (Shriberg & Kwiatkowski, 1982).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Por su parte, Oropeza (1987) analizó, desde una perspectiva generativista, el sistema consonántico en niños cuyas edades fluctuaban entre los 2;0 y los 6;6 años. Bernhardt et al (2015) discuten la estructura de las palabras de niños de educación preescolar y hacen una comparación entre aquéllos que presentan un desarrollo típico y los que exhiben desarrollo atípico, incursionando también en el nivel fonológico.…”
Section: Adquisición De Las Consonantes Líquidas En El Español De Méxicounclassified